MILK COMPOSITION OF CROSSBRED AND DESI CATTLE MAINTAINED IN THE SUB-TROPICAL HIGH RANGES OF KERALA - Bindya Liz Abraham; S.L. Gayathri (Indian Journal of Veterinary and Animal Sciences Research, 2024)
A comparison of milk yield and composition of various indigenous and crossbred cattle was undertaken to evaluate their performance in the subtropical high altitudes of Kerala. A total of 173, 95, 63 and 63 morning milk samples from 42 CBHF, 12 Vechur, six Sahiwaland six Kankrej cows of early second lactation were analyzed for total solids, fat, solids-not-fat, lactose, protein and chloride by conventional  methods. Least squares analysis revealed that breed and test-day climate significantly influenced the milk yield and composition (P >0.05). The mean lactation yield in Vechur, Sahiwal, Kankrej and CBHF were 514.62 ± 42.87 Kg, 1025.65 ± 358.15 Kg, 1102.45 ± 358.15 Kg and 1763.93 ± 128.16 Kg respectively. Kankrej had higher fat and total solids while Vechur had higher SNF, protein and lactose (P >0.05). Vechur had lesser seasonal fluctuations in major constituents, indicating it’s adaptability and climatic resilience as the native breed of Kerala.